The Discourse and Reality of Carbon Dioxide Removal: Toward the Responsible Use of Metaphors in Post-normal Times - Castree, Noel (Frontiers in Climate, 2020)
There’s little doubt that a variety of CDR techniques will be employed worldwide in the decades and centuries to come. Together, these techniques will alter the character and functioning of the biosphere, hydrosphere, cryosphere, pedosphere and atmosphere. However, for the moment CDR exists more in the realm of discourse than reality. Its future roll-out in many and varied forms will depend on a series of discussions in the governmental, commercial and civic spheres. Metaphor will be quite central to these formative discussions. Metaphors serve to structure perceptions of unfamiliar phenomena by transferring meaning from a recognised ‘source’ domain to a new ‘target’ domain. Metaphors help to govern future action by framing present-day understandings of a world to come. To govern metaphor itself may seem as foolhardy as attempting to sieve water or converse with rocks. Yet by rehearsing some old lessons about metaphor we stand some chance of responsibly steering its employment in unfolding debates about CDR techniques and their practical governance globally. This Perspective identifies some key elements of metaphor’s use that will require attention in the different contexts where CDR techniques presently get (and will in future get) discussed meaningfully. Various experts involved in CDR development and deployment have an important, though not controlling, role to play in how it gets metaphorised. This matters in our age of populism, rhetoric, misinformation and disinformation where the wilful (mis)use of certain metaphors threatens to depoliticise, polarise or simplify future debates about CDR.